Institutions of Higher Education as Multi-Product Firms: Economies of Scale and Scope - Cohn, Elchanan; Rhine, Sherrie L. W.; Santos, Maria C. (The Review of Economics and Statistics, 1989)
Elchanan Cohn, Sherrie L. W. Rhine, Maria C. Santos, Institutions of Higher Education as Multi-Product Firms: Economies of Scale and Scope, The Review of Economics and Statistics, Vol. 71, No. 2 (May, 1989), pp. 284-290